2019
DOI: 10.1002/term.2809
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic three‐dimensional levitated primary cell culture system for the development of secretory salivary gland‐like organoids

Abstract: Salivary gland (SG) hypofunction and oral dryness can be induced by radiotherapy for head and neck cancers or autoimmune disorders. These are common clinical conditions that involve loss of saliva-secreting epithelial cells. Several oral complications arise with SG hypofunction that interfere with routine daily activities such as chewing, swallowing, and speaking. Hence, there is a need for replacing these saliva-secreting cells. Recently, researchers have proposed to repair SG hypofunction via various cell-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Tissue engineering of 3-dimensional (3-D) primary HSG cultures for transplantation into afflicted patients represents another regenerative strategy to restore salivary gland function (Lombaert et al, 2017). Because primary human salivary gland cells undergo loss of cell-specific protein expression and biological function when cultured in a monolayer (Jang et al, 2015), development of 3-D culture strategies using Matrigel (Feng et al, 2009;Maria et al, 2011), collagen-Matrigel (Joraku et al, 2007Pringle et al, 2016), hyaluronic acid-based hydrogels (Pradhan-Bhatt et al, 2013) and magnetic 3-D levitation (Ferreira et al, 2019) has been explored to maintain salivary gland cell function in culture. Indeed, transplantation of 3-D cultured, primary human salivary gland cells has been shown to ameliorate radiation-induced salivary gland dysfunction in mice (Pringle et al, 2016).…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…Tissue engineering of 3-dimensional (3-D) primary HSG cultures for transplantation into afflicted patients represents another regenerative strategy to restore salivary gland function (Lombaert et al, 2017). Because primary human salivary gland cells undergo loss of cell-specific protein expression and biological function when cultured in a monolayer (Jang et al, 2015), development of 3-D culture strategies using Matrigel (Feng et al, 2009;Maria et al, 2011), collagen-Matrigel (Joraku et al, 2007Pringle et al, 2016), hyaluronic acid-based hydrogels (Pradhan-Bhatt et al, 2013) and magnetic 3-D levitation (Ferreira et al, 2019) has been explored to maintain salivary gland cell function in culture. Indeed, transplantation of 3-D cultured, primary human salivary gland cells has been shown to ameliorate radiation-induced salivary gland dysfunction in mice (Pringle et al, 2016).…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…In addition, the Souza's group also proposed a magnetic 3D levitation (M3DL) culture system that allowed primary salivary gland-derived cells (SGDCs) to produce their own extracellular matrix for generating salivasecreting organoids or miniglands ( Figure 3b). [86] The relevant organoids exhibited uniform spherical morphology with increased cell viability and pro-mitotic cells. More importantly, M3DL system could increase the expression of related functional proteins compared to conventional salisphere cultures.…”
Section: Magnetic Suspensionmentioning
confidence: 99%
“…Therefore, a novel operable 3D culture technology named magnetic levitation culture based on nanoparticles is proposed ( Figure 1e). [85][86][87][88][89][90] It was demonstrated that the magnetic suspension method could enhance the viability of bovine secondary follicles, antrum formation, and lower degeneration rates. [85] Also, the system has the potential to be an alternative in vitro follicular culture in several species, including humans.…”
Section: Magnetic Suspensionmentioning
confidence: 99%
“…A magnetic field allows for the directed assembly of magnetic particles into chains, stiffening the mechanical properties of the microenvironment, resulting in MSCs with increased area. (B) Internalized magnetic NPs in salivary gland-derived cells accelerate spheroid formation by an external magnetic field, yielding faster and more reproducible spheroids with lower necrosis (Ferreira et al, 2019). (C) Internalized magnetic NPs allow remote manipulation of embryoid bodies and direct the differentiation of embryonic stem cells toward a mesodermal cardiac identity (adapted from Du et al, 2017).…”
Section: Using Nps To Build 3d Spheroids and Shape Complex Geometriesmentioning
confidence: 99%
“…In contrast, the use of magnetic NPs was shown to increase forces and effective manipulation range, which enabled the formation of highly reproducible spheroids. By applying a magnetic field, magnetized salivary gland-derived cells were guided to the air-media interface where they agglomerated to form spheroids which eventually differentiated into gland-like organoids ( Figure 2B) (Ferreira et al, 2019). This approach provided rapid cellular assembly while foregoing the need for scaffold materials, rendering this a promising advance towards salivary gland repair.…”
Section: Using Nps To Build 3d Spheroids and Shape Complex Geometriesmentioning
confidence: 99%